The association between maximal muscle strength, disease severity and psychopharmacotherapy among young to middle-aged inpatients with affective disorders – a prospective pilot study - Ramming, Hannah; Theuerkauf, Linda; Hoos, Olaf; Lichter, Katharina; Kittel-Schneider, Sarah (BMC Psychiatry, 2024)
Background: Motor alterations and lowered physical activity are common in affective disorders. Previous research has indicated a link between depressive symptoms and declining muscle strength primarily focusing on the elderly but not younger individuals. Thus, we aimed to evaluate the relationship between mood and muscle strength in a sample of N = 73 young to middle-aged hospitalized patients (18–49 years, mean age 30.7 years) diagnosed with major depressive, bipolar and schizoaffective disorder, with a focus on moderating effects of psychopharmacotherapy. The study was carried out as a prospective observational study at a German psychiatric university hospital between September 2021 and March 2022. Methods: Employing a standardized strength circuit consisting of computerized strength training devices, we measured the maximal muscle strength (Fmax) using three repetitions maximum across four muscle regions (abdomen, arm, back, leg) at three time points (t1-t3) over four weeks accompanied by psychometric testing (MADRS, BPRS, YRMS) and blood lipid profiling in a clinical setting. For analysis of psychopharmacotherapy, medication was split into activating (AM) and inhibiting (IM) medication and dosages were normalized by the respective WHO defined daily dose. Results: While we observed a significant decrease of the MADRS score and increase of the relative total Fmax (rTFmax) in the first two weeks (t1-t2) but not later (both p <.001), we did not reveal a significant bivariate correlation between disease severity (MADRS) and muscle strength (rTFmax) at any of the timepoints. Individuals with longer disease history displayed reduced rTFmax (p =.048). IM was significantly associated with decreased rTFmax (p =.032). Regression models provide a more substantial effect of gender, age, and IM on muscle strength than the depressive episode itself (p <.001). Conclusions: The results of the study indicate that disease severity and muscle strength are not associated in young to middle-aged inpatients with affective disorders using a strength circuit as observational measurement. Future research will be needed to differentiate the effect of medication, gender, and age on muscle strength and to develop interventions for prevention of muscle weakness, especially in younger patients with chronic affective illnesses.
CRIS-Team Scopus Importer:2026-04-08
Keywords: Affective disorder; Bipolar disorder; Depression; Muscle strength; Physical activity; Psychopharmacotherapy; Young